(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the patterns and localization of ischemic cerebral stroke in patients who are not using antiplatelets drugs, presenting to tertiary care hospital. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at the Department of Medicine, KTH, Peshawar from 15th January 2021 to 15th July 2021. Materials and Methods: A total of 101 patients of both gender with Ischemic stroke, who were not using any antiplatelets drugs were included in the study. All patients were sent to CT scan and patterns and localization of ischemic stroke was noted. Results: Age range in this study was from 40 to 70 years with mean age of 58.435±4.79 years, mean duration of stroke 15.584±2.51 hours and mean weight was 87.604±5.25 Kg. Single lesion was seen in 45.5% patients, two lesion 9.9%, three lesion 35.6%, corona radiata infarct 31.7%, large hemispheric 13.9%, internal capsule 7.9%, Striatocapsular junction 3%, cerebellum 5% and pons was 22.8%. Conclusion: Single lesion (Pattern 1) was more prevalent and Corona radiata localization was mostly observed in our study.